NTPC public offer - Barua, S. K. (Samir K.); Agarwalla, Sobhesh Kumar (London : Indian Institute of Management, Ahmedabad, 2010)
The National Thermal Power Corporation (NTPC) was the first case of large scale disinvestment by the Indian government. However, the shares did not fare well in the FPO or Follow-on Public Offer due to the volatility of the markets in 2009-10 and the Indian government's decision to use the French auction system. The reader is then invited to consider what lessons can be learned from the disinvestment in NTPC as the Indian Government also prepares to disinvest from two other companies: the Rural Electrification Corporation and the National Mineral development Corporation.
Originally published in Barua, S., & Agarwalla, S. (2010) NTPC Public Offer. F&A0489. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Thermal Power Corporation (India) -- Case studies; Disinvestment -- India -- Case studies; Going public (Securities) -- India -- Case studies